2021
DOI: 10.1186/s13018-021-02269-w
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between growth differentiation factor 5 (rs143383) gene polymorphism and knee osteoarthritis: an updated systematic review and meta-analysis

Abstract: Background A great deal of evidence has supported that growth differentiation factor 5 (GDF5) is associated with the occurrence of knee osteoarthritis (KOA), while their results are not consistent. In the present study, we aimed to explore the association between GDF5 gene polymorphism and KOA for a more credible conclusion. Methods Comprehensive literature searches were carried out in English databases, including PubMed, Embase, Web of Science (WO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…On the other hand, the C allele of GDF‐5 (rs143383) seems to be associated with protection against knee OA and/or hand OA. Also, the results showed that the allele C (or genotype CC) of the GDF‐5 polymorphism (rs143383) protected against knee OA occurrence in Caucasian, Asian, and African populations 8,29,31 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, the C allele of GDF‐5 (rs143383) seems to be associated with protection against knee OA and/or hand OA. Also, the results showed that the allele C (or genotype CC) of the GDF‐5 polymorphism (rs143383) protected against knee OA occurrence in Caucasian, Asian, and African populations 8,29,31 …”
Section: Discussionmentioning
confidence: 99%
“…Also, the results showed that the allele C (or genotype CC) the GDF-5 polymorphism (rs143383) protected against knee OA occurrence in Caucasian, Asian, and African populations. 8,29,31 The estrogen receptor α (ESRα) gene regulates cellular signal pathways in vivo and bone mass in skeletal systems. Moreover, human ESRα, a member of the nuclear receptor superfamily of ligand-activated transcription factors that regulates gene expression and function, is one of the critical mediators of hormonal response in estrogen-sensitive tissues.…”
Section: Gdf-5 (Rs143383)mentioning
confidence: 99%
See 2 more Smart Citations
“…The GDF5 polymorphism rs143383 is reproducibly associated with OA, and this year was associated with OA-risk in the Kurdish population 1 . Oddly, in two meta-analyses examining the association of rs143383 with knee OA (KOA) in Asian individuals contradictory findings were observed 2,3 , while a new study in a Chinese Han population did find a link with KOA 4 . rs143383 is located in the 5 0 UTR of GDF5 and is associated with differential allelic expression of the gene, via altered DNA-binding of several transcriptional repressors 5 .…”
Section: Geneticsmentioning
confidence: 99%